Plasma-assisted catalysis for volatile organic compounds abatement - Magureanu, Monica; Mandache, Nicolae B.; Eloy, Pierre; Gaigneaux, Eric M.; Parvulescu, Vasile I. (Applied catalysis. B, Environmental, 2005)
A dielectric barrier discharge (DBD) combined with Mn-based phosphate catalysts placed downstream of the plasma reactor was investigated experimentally for total oxidation of toluene in air. The discharge was initiated by high voltage pulses of 18kV amplitude and 12–13ns rise time. The pulse frequency increased from 14 to 80Hz, for applied voltages in the range 18–28kV. Discharge currents up to 100 A and approximately 50ns duration were obtained. No other hydrocarbons except toluene were detected in the effluent gas. The yield of carbon dioxide formed in the discharge was up to 24%. As catalysts, MnPO4, Mn-APO-5 and Mn-SAPO-11 were tested, for temperatures up to 400°C. Under purely catalytic conditions, the best behavior for toluene total oxidation was found for Mn-SAPO-11, with a CO2 yield up to 33%, at 400°C. The combined application of plasma and catalysis showed a remarkable synergetic effect, even at low temperature, up to 100°C, where the catalysts alone are not active. In this range, the CO2 yield increased up to 41%, for the Mn-SAPO catalyst. At 400°C the highest CO2 yield was obtained for MnPO4, reaching 68%. The synergetic effect observed for the plasma–catalyst combination is attributed to ozone radicals formed in the discharge, which decompose on the catalyst surface, greatly contributing to toluene total oxidation.